Influence of population and general practice characteristics on prescribing of minor tranquilisers in primary care - Wagner AC; Hann M; Ashcroft DM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Prevalence of generalised anxiety disorders is widespread in Great Britain. Previous small-scale research has shown variations in minor tranquiliser prescribing, identifying several potential predictors of prescribing volume. Objective: This study aimed to investigate the relationship between general practice minor tranquiliser prescribing rates and practice population and general practice characteristics for all general practices in England.Methods: Multiple regression analysis of minor tranquiliser prescribing volumes during 2004/2005 for 8,291 English general practices with general practice and population variables obtained from the General Medical Services (GMS) statistics, Quality and Outcomes Framework (QOF), 2001 Census and 2004 Index of Multiple Deprivation (IMD). Results: The highest rates of minor tranquiliser prescribing were in areas with the greatest local deprivation while general practices situated in areas with larger proportions of residents of black ethnic origin had lower rates of prescribing. Other predictors of increased prescribing were general practices with older general practitioners and general practices with older registered practice populations.Conclusion: Our findings show that there is wide variation of minor tranquilisers prescribing across England which has implications regarding access to treatment and inequity of service provision. Future research should determine the barriers to equitable prescribing amongst general practices serving larger populations of black ethnic origin.